From Luminosity to Love: Metaphysics and Empathy in Hearer of the Word - Duns, Ryan G. (Theological studies, 2021)
Can a metaphysical argument for God’s existence warrant affirming not only that God is but that God is, and creates out of, love? In Hearer of the Word, Karl Rahner makes such an argument. After reaffirming the distinctively metaphysical character of Rahner’s philosophy of religion, the article revisits his cosmological argument’s attempt to ground the intelligibility of being in God’s love. Drawing on the work of Edith Stein, I identify an implicit “empathic logic” at work in Rahner’s metaphysics, a logic that enables him to recognize the givenness and intelligibility of creation as an expression of God’s love.